PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO ZAM-ZAM DARA KOTA BIMA - Sri Ernawati; Sari, Aenun (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Implementation of quality service management and promotions in accordance with consumer preferences can influence consumer purchasing decisions. This study aims to see the effect of service quality and promotion on purchasing decisions at the Zam-Zam store in Bima City. This type of research is associative, the research instrument uses a questionnaire with a Likert scale. The population used in this study were all consumers at the Zam-Zam store whose number was unknown (unknown population). The number of samples used in this study were 50 respondents using a purposive sampling technique. Data collection techniques with observation, questionnaires, and literature study. Data analysis techniques by carrying out validity tests, reliability tests, multiple linear regression tests, correlation coefficients, determination tests, t tests, and f tests. The results of this study indicate that service quality and promotion have a significant effect on purchasing decisions at the Zam-Zam store in Bima City.